Evaluación de la panca de arroz amonificada con urea, como suplemento alimenticio en ganaderías vacunas del cantón Baba, Los Ríos - Tomalá Muñoz, Jaime Javier (2020)
The experimental work was carried out at the La Delia cattle ranch, Pimocha parish of the Baba canton. The objective was to evaluate the rice husk ammonified with urea, as a food supplement in milk-producing cows. Three cows between 80 and 100 days of lactation, urea, rice paddy and ammonified rice paddy were used. The rice husk ammonified with urea was evaluated as a feed supplement in milk-producing cows. The deductive experimental method and a completely randomized design (DCA) were applied, with three treatments and three repetitions. For the evaluation and comparison of the mean of the treatments, the Tukey test was performed at 5% significance. Each experimental unit consisted of one animal. The variables evaluated were: the consumption of panca ammonified with urea in the different treatments and the production of milk with the supplementation of panca ammonified with urea. The analysis of variance did not detect significant differences for the evaluations of the first, third and sixth days and highly significant differences for the rest of the treatments. The highest average was reported in the evaluations of the second (10.0 kg), fourth (9.0 kg), fifth (8.0 kg), seventh (9.7 kg), eighth (9.9 kg) days , ninth (10.3 kg), tenth (9.7 kg), eleventh (10.5 kg), twelfth (10.6 kg), thirteenth (9.9 kg), fourteenth (10.2 kg) and fifteenth (10.0 kg) with the use of ammonified bread, statistically superior to the other treatments. the cows at the beginning of the trial had an average daily milk production of 2.5 liters and at the end the average was 5 liters.